Pineapple (Ananas comosus L. Merr) cultivation under minimum tillage and conventional tillage in San Carlos, Costa Rica. - Rojas-Acuña, Luis Antonio (2004)
The establishment and development of apineapple cultivation sowed in minimum tillage andconventional tillage was evaluated in San Carlos, Costa Rica.The work carried out consisted of a description of thepreparation of the land, and an analysis of organic matter,microorganisms and arthropods, nematodes, and mortality ofplants; an analysis of production costs was also made. Theconventional preparation of soil was carried out between fourand five months after paraquat application, while inminimum tillage the time preparation of soil was of twomonths after herbicide application. Also, in minimum tillagethe residues of the previous plantation deposited in theinternal streets can serve as a source of inoculum of pests anddiseases, besides hindering the drainage. The population ofmicroorganisms (bacterias, actinos and fungi) was higher inminimum tillage. In the analysis of arthropods, theconventional tillage showed higher populations of Oribatidaand Collembola, while in minimum tillage there was a largerpopulation of mites and larvae of Elateridae; the populationof Scarabeidae was similar in both tillage systems. Thepopulation of nematodes in soils and roots was also relativelylow. The main cause of plant mortality was due to diseasesknown as “rots” caused by the complex Phytophthora-Erwinia; but the incidence was low in both tillage systems.No significant differences were observed in plant heighteither. The costs of preparation of the land in minimumtillage were 50 % lower than those of the conventional tillage.